2023
DOI: 10.1186/s12885-023-11735-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors enhanced the antitumor efficacy of disitamab vedotin for patients with HER2-positive or HER2-low advanced or metastatic gastric cancer: a multicenter real-world study

Caiyun Nie,
Weifeng Xu,
Yanwei Guo
et al.

Abstract: Background Novel ADC drugs provide a new therapeutic strategy for gastric cancer.The present study aimed to analyze the clinical efficacy and drug toxicities of disitamab vedotin (RC48) plus immune checkpoint inhibitors(ICIs) and RC48 as third-line therapies and beyond for advanced and metastatic gastric cancer patients. Methods This was an observational multicenter real-world study.From August 2021 to January 2022,patients with HER2-positive or HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Numerous clinical studies have demonstrated the efficacy of RC48 in treating patients with either locally advanced or metastatic HER2-overexpressing gastric cancer, including adenocarcinoma of the gastroesophageal junction, following a minimum of two systemic chemotherapy courses (27)(28)(29). It is also effective for those with advanced or metastatic uroepithelial cancer who have previously received platinum-containing chemotherapy and have shown HER2 overexpression of either 2+ or 3+ on immunohistochemistry (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have demonstrated the efficacy of RC48 in treating patients with either locally advanced or metastatic HER2-overexpressing gastric cancer, including adenocarcinoma of the gastroesophageal junction, following a minimum of two systemic chemotherapy courses (27)(28)(29). It is also effective for those with advanced or metastatic uroepithelial cancer who have previously received platinum-containing chemotherapy and have shown HER2 overexpression of either 2+ or 3+ on immunohistochemistry (29,30).…”
Section: Discussionmentioning
confidence: 99%